Pengembangan Media Belajar yang Interaktif Berbasis Web untuk Mengatasi Masalah Buta Aksara pada Siswa SD di Kabupaten Bekasi - Rian Andrian; Alief Iksan Al Ghani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research project is concerned with the development of web-based interactive learning media with the objective of reducing illiteracy among elementary school students in the Bekasi District. In light of the pivotal role of literacy in the era of society 5.0 and the ambitious